2010
DOI: 10.1080/14733141003712301
|View full text |Cite
|
Sign up to set email alerts
|

Trainee nondisclosure in supervision: What are they not telling you?

Abstract: Aims: The purposes of this study were to examine: (1) the content of and reasons for trainee nondisclosure in supervision, and (2) the influence of trainee anxiety and perception of the supervisory working alliance on amount of nondisclosure and willingness to disclose. Method: As the focus of the study was a single supervision session, qualitative and quantitative data were collected from 204 trainees about their most recent supervision session. Results: Within the single supervision session on which they rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
198
4
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(229 citation statements)
references
References 20 publications
24
198
4
3
Order By: Relevance
“…In early work, Ladany et al (1996) found that supervisee nondisclosure was related to poor SRs, supervisor incompe tence, and fear of negative evaluation. More recently, Mehr, Ladany, and Caskie (2010) suggest that failure to disclose in supervision may have a direct impact on therapy outcomes including alliance ruptures and premature termination of therapy. However, the content of supervisee nondisclosure is most commonly related to dif ficulties in the SR, such as perceived incompetence of the supervisor (Lemoir, 2013;Reichelt, 2009), unclear expectations, and supervisor unprofessionalism (Inman et al, 2011).…”
Section: How Do We Sustain An Effective Sr?mentioning
confidence: 99%
“…In early work, Ladany et al (1996) found that supervisee nondisclosure was related to poor SRs, supervisor incompe tence, and fear of negative evaluation. More recently, Mehr, Ladany, and Caskie (2010) suggest that failure to disclose in supervision may have a direct impact on therapy outcomes including alliance ruptures and premature termination of therapy. However, the content of supervisee nondisclosure is most commonly related to dif ficulties in the SR, such as perceived incompetence of the supervisor (Lemoir, 2013;Reichelt, 2009), unclear expectations, and supervisor unprofessionalism (Inman et al, 2011).…”
Section: How Do We Sustain An Effective Sr?mentioning
confidence: 99%
“…We recommend communicating the value of this approach to the trainee at the outset of supervision to further create a sense of shared accountability with respect to obtaining the goals of the supervisory relationship. Obtaining candid information from trainees can be difficult (Mehr, Ladany, & Caskie, 2010), and supervisors must consider the inherent power differential; however, a strong supervisory relationship between the supervisor and trainee and an expectation of the reciprocal nature of feedback is hypothesized to counteract this limitation.…”
Section: Evaluation Of Performance Expectationsmentioning
confidence: 99%
“…Factors include the fear of being judged and evaluated influencing the ability to disclose in supervision; and there is evidence of a positive correlation between the quality of the supervisory relationship as experienced by the supervisee, and the level of disclosure (Webb & Wheeler, 1998). Mehr, Ladany, and Caskie (2010) found that 'supervisees tended not to disclose supervision-related issues more so than clinical issues ' (pp. 107-110), and they highlight the importance of the working alliance in supervision as a mediating factor in determining the disclosure of issues.…”
Section: Introductionmentioning
confidence: 95%